THE INFLUENCE OF INTELLIGENCE TESTS ON HUMAN THINKING - Narkulov , Xusan Ismoilovich (Educational Research in Universal Sciences, 2023)
Intellectual talent, in turn, in psychology, refers to the possibility of creative intellectual activity associated with the subjective and objective creation of new ideas, the use of non-standard approaches in developing problems, and sensitivity to the main, most promising directions of the search for solutions. is considered as a special case of individual mental resources (primarily mental).